SOLUCIÓN NUMÉRICA DEL ATRACTOR DE LORENZ POR EL MÉTODO DE RUNGE-KUTTA-FEHLBERG - Llosa Demartini, Melchor (2004)
There is no an explicit solution for is proposed problem in 1963 by Lorentz. Generally, this system of differentials equations is solved by the method oftrapezoidal integration with extrapolation of Richardson or by the improved method of Euler. In this work an altemative solution by the method of Runge Kutta Fehlberg ís presented, which requires only six evaluat.ions ofthe function, thus reducing the time ofcalculation.